Carotenoids in the pulp and peel of bananas from 15 cultivars in two ripening stages - Fernandes Aquino, César; Chamhum Salomão, Luiz Carlos; Pinheiro-Sant’ana, Helena Maria; Machado Rocha Ribeiro, Sônia; Lopes De Siqueira, Dalmo; Cecon, Paulo Roberto (Revista Ceres, 2025)
The current study aims to evaluate the occurrence and concentration of carotenoids in the pulp and peel of 14 banana and one plantain cultivars in two ripening stages. We analyzed the occurrence and content of lutein, αcarotene, β-carotene, β-cryptoxanthin, and lycopene – by high performance liquid chromatography with UV-visible detection, the content of total carotenoids by spectrophotometry. In the unripe pulp, the ‘Ouro’ cultivar stood out with lutein concentration 13 times higher than that of the ‘Marmelo’. As for á-carotene and β-carotene, ‘Terrinha’ plantain stood out with mean concentration of 1195.30 and 1126.11 µg (100 g MF-1), respectively. Total carotenoids ranged from 159.66 to 2553.51 µg (100 g MF-1) in ‘Caipira’ and ‘Terrinha’, respectively. In the ripe pulp there was 36% increase in the lutein content in comparison to the unripe pulp and there was 7.3 and 8.5% reduction in α-carotene and β-carotene levels, respectively. The total carotenoid concentration in the ripe pulp was 17% higher than that found in the unripe pulp. The unripe peel showed lutein predominance, although ‘Terrinha’ stood out with higher α-carotene and µcarotene concentrations than those found in the other cultivars. Lutein concentration hardly changed due to fruit ripening; however, there was slight reduction in α-carotene and β-carotene concentrations.